Climate Change and Federal Aid Disbursements After Hurricane Harvey: An Extreme Event Attribution Analysis - Kevin T. Smiley; Ilan Noy; Michael F. Wehner; Christopher C. Sampson; Oliver E.J. Wing; KayLynn Larrison (CESifo GmbH, 2024)
The role climate change plays in increasing the burden on governments and insurers to pay for recovery is an area not examined by extreme event attribution research. To study these impacts, we examine the impacts of climate change attributed flooding on federal disaster aid disbursement in Harris County, Texas following Hurricane Harvey. Our approach uses flood models to estimate in dollars the amount of flood damages not attributable to climate change and the amount of flood damages attributable to climate change under two climate change attribution scenarios estimated in peer reviewed studies (20% and 38% additional rainfall due to climate change). These estimates are combined with census tract-level disbursement data for FEMA's National Flood Insurance Program (NFIP) and the Individual Assistance (IA) part of the Individuals and Households Program. We employ spatial lag regression models and estimate direct and spatial spillover effects to analyze the relationship between a tract's flood damages – both attributed and not attributed to climate change – and federal disaster aid. We find that both types of flood damage shape federal aid disbursements, with impacts varying based on the percentage of rainfall attributed to climate change and the specific aid program. Our discussion centers on how these differences might reflect what we term "typical" and "(a)typical" flooding.
Keywords: Q54; 330; extreme weather attribution; federal disaster aid; FEMA; NFIP; Hurricane Harvey